2016
DOI: 10.1139/cjas-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin as a predictor for carcass composition in growing lambs

Abstract: Abstract:The experiment was conducted on 30 single born Polish Merino ram lambs. At the age of 112 d, 10 ram lambs were slaughtered at 20 kg (group 1), 25 kg (group 2), and 30 kg (group 3) live weight. Plasma leptin increased between 20 and 25 kg, as well as 25 and 30 kg live weight. The differences between group 1 vs. group 3 and group 2 vs. group 3 were statistically important (P < 0.001). The lack of differences in meat content of the pelvic limb between the groups and, at the same time, the lower fat conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Also, a similar result was reported by Altmann et al (2005) for different breeds (East Frisian and Blackheaded Mutton  East Frisian crosses). On the other hand, Kuznicka et al (2017) reported that fat thickness over the eye loin did not change with live weight in merino male lambs. It stood out that back fat thickness was faster in increase than serum leptin levels by BW in Awassi male lambs.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, a similar result was reported by Altmann et al (2005) for different breeds (East Frisian and Blackheaded Mutton  East Frisian crosses). On the other hand, Kuznicka et al (2017) reported that fat thickness over the eye loin did not change with live weight in merino male lambs. It stood out that back fat thickness was faster in increase than serum leptin levels by BW in Awassi male lambs.…”
Section: Resultsmentioning
confidence: 90%
“…For instance, Higashiyama et al (2003) reported serum leptin level was positively related to carcase fatness (r ¼ 0.69, p < .05) in Japanese Black steers and Altmann et al (2006) reported a lower correlation coefficient (r ¼ 0.41, p < .05) for male lambs at 40 kg BW. Also, Kuznicka et al (2017) reported an other lower correlation coefficient (r ¼ 0.41, p < .05) but it was for low weight (20, 25 and 30 kg) BWs male merino lambs. These results mean that fat accumulation for different tissues can occur at different BWs in different breed and species.…”
Section: Relationship Between Leptin and Fat Tissues Amountmentioning
confidence: 85%
“…There was no effect of leptin concentration on fertility rate, but twins rates increased in the group of ewes with medium leptin concentration, reaching 23.05%.explains it the recent research suggests that leptin plays an important role in female reproduction, including ovarian function control [8]. Leptin is important in signaling nutritional status to the mammalian central reproductive axis and appears to be a permissive factor in the initiation of puberty at least in some cases [9]. We observe a correlation between leptin hormone concentration and progesterone and estrogen concentrations, with the concentrations of the two hormones increasing by 0.55 and 0.22, respectively, in ewes with medium leptin concentrations compared to ewes with low and high leptin concentrations.This is consistent with a study that found a direct relationship between progesterone hormone levels [10].…”
Section: Resultsmentioning
confidence: 95%
“…Leptin concentrations are strongly associated with adipocyte mass. Adipocyte mass increases, and simultaneously concentrations of leptin also increase, because adipocyte size may influence leptin synthesis [59,60]. Serum concentrations of leptin were positively correlated with a marbling score, kidney, pelvic, and heart fat (KPH), fat depth, quality grade, and yield grade of meat [61].…”
Section: Leptinmentioning
confidence: 99%